Effectiveness ISO 9000 quality management practices : A case study of academic libraries in Malaysia - Taib, Che Azlan; Osman, Nor Hasni; Ahmad, Hartini (KBD Publications, 2009)
The paper aims to study the effectiveness ISO 9000 quality management practices on customer satisfaction levels toward academic library services. The exploratory research in this paper focuses on the link between ISO 9000 practices and an area of customer satisfaction, namely, MUDI (accessibility); KESE (suitable); SEAD (availability); KEBE (effectiveness); KECE (efficiency); BODI (reliability) and KESA (validity), that has received limited attention in prior studies. The research supports the idea that ISO 9000 standards are a guideline for the implementation of quality management in any organizations whether in library services.